Músicas e videoclipes de Criolo em resistência ao dispositivo de racialidade : audiovisualidades insurgentes no rap - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research aims to develop a discursive analysis of verbal-visual utterances present in the lyrics and music videos of rapper Criolo. The research corpus to be described and analyzed consists of the works: Cleane (Criolo, 2021) and Pretos ganhando dinheiro incomoda demais (Criolo, 2022), with the aim of broadening the understanding of the analyzed material. In the description and analysis of this research material, the archaeogenealogical methodology (Foucault, 2010, 2014, 2020, 2023) will be employed, and thus, through Discourse Analysis, the utterances that emerge in this verbal-visual composition will be examined. We will mobilize the concept of discourse genre (Bakhtin, 2003) to explore the musical genre of rap in its discursive potentialities and practices of subjectivation. The utterances to be analyzed will be described through the functioning of the concept of raciality device (Carneiro, 2023), focusing on aspects related to racism and culture (Fanon, 2018; Nascimento, 2016; Kilomba, 2019; Gomes, 2003; Hall, 2023). For the description and analysis of the images, we will draw on research that applies the relations between discourse and image (Courtine, 2011; Milanez, 2013). We seek to understand how rapper Criolo, in the Brazilian historical and social context, articulates utterances in his lyrics and music videos, using the discourse genre of rap as a tool to denounce racism. Analyzed through the lens of Foucault's archaeogenealogical methodology, these works reflect, act upon, and confront the functioning of Sueli Carneiro's raciality device, contributing to the deconstruction of this mechanism, the reaffirmation of Black identity, and the advancement of studies on rap and race relations in Brazil. At the end of the research, we concluded that the analyzed corpus demonstrates the social functioning of the raciality device in Brazilian society. It was possible to observe how the utterances present in Criolo's works enable resistance to this device, reinforcing the importance of rap as a tool for social transformation and anti-racist struggle.
Songs and music videos by Criolo in resistance to the racial dispositif : insurgent audiovisualities in rap
Keywords: Análise do discurso; Dispositivo de racialidade; Rapper Criolo; Rap; Discourse analysis; Raciality device; Rapper Criolo; LINGUISTICA, LETRAS E ARTES::LINGUISTICA